2008
DOI: 10.1002/dys.369
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of word‐level literacy amongst Grade 3 children in five diverse languages

Abstract: Groups of Grade 3 children were tested on measures of word-level literacy and undertook tasks that required the ability to associate sounds with letter sequences and that involved visual, auditory and phonological-processing skills. These groups came from different language backgrounds in which the language of instruction was Arabic, Chinese, English, Hungarian or Portuguese. Similar measures were used across the groups, with tests being adapted to be appropriate for the language of the children. Findings indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
1
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 37 publications
4
50
1
9
Order By: Relevance
“…This is due to children committing writing appropriation "errors" during the apprenticeship until, progressively, dominate the spelling system in a securer way (2,8,18) . one (9) . The two refer that both the phonological processes and the spelling ones are important to the writing apprenticeship, because the standard of phoneme-grapheme conversion can be learned with the increase of the exposition to the frequency of the occurrence and the use of the spelling annotations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to children committing writing appropriation "errors" during the apprenticeship until, progressively, dominate the spelling system in a securer way (2,8,18) . one (9) . The two refer that both the phonological processes and the spelling ones are important to the writing apprenticeship, because the standard of phoneme-grapheme conversion can be learned with the increase of the exposition to the frequency of the occurrence and the use of the spelling annotations.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors (8,9) concluded both the phonological processes and the spelling ones are important to the writing apprenticeship. In their researches, they observed that the standard of letters in new words of higher frequency were learned more easily, as the phonological standards that occurred with higher frequency in words were also related to letters more quickly.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors 8,9 concluded that both the spelling and phonological processes are important for learning of writing, when in their research observed that the patterns of letters in new words more frequently were more easily learned, as well as the phonological patterns that occurred more often in words were also related to the letters more quickly.…”
Section: Introductionmentioning
confidence: 99%
“…These components, ie, phonological working memory and access to mental lexicon enable the processing and organization of language. Likewise, they are requested by the central executive component in carrying out any task, including phonological awareness and phoneme-grapheme association [11][12][13].…”
Section: Introductionmentioning
confidence: 99%